Bureaucracy, Community, and Land: The Resettlement of Meos in Mewat, 1949–50. Issue 1 (28th February 2019) - Ankit, Rakesh
Abstract: This article documents in detail hitherto unavailable what Shail Mayaram called an "onslaught by the modern bureaucracy of the postcolonial state" on the liminally placed Meo community in the Mewat region, comprising the former princely states of Alwar and Bharatpur and the Gurgaon district of the former province of East Punjab. A people well-described as "in-between Hinduism and Islam, " the Meo community found itself, at a time of "two-nation" theory and consequent "partition politics, " a misfit. This article begins in 1949, when existing accounts of the story of the Meos end and traces the fraught process of their reterritorialization on their own land, now part of a partitioned nation state. Given the current ascendant culturally nationalist Indian state and society, it represents the Mewat of 1949–50 as a community lab of the early Indian nation state; tests its claims of parity, equality, and freedom; and provides a "prehistory" of the contemporary violence there.